(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Preterm and low-birth-weight infants are often assessed using standard growth charts. The Fenton 2013 chart, based on retrospective data from developed countries, and the INTERGROWTH-21st (IG-21st) chart, based on multiethnic prospective data, are commonly used standards. This study compares neonatal growth patterns using both charts and examines associated morbidities. Materials and Methods: We conducted a prospective observational study in the neonatal intensive care unit (NICU) of Sri Guru Ram Das Institute of Medical Sciences (July 2024–Dec 2025). All inborn and outborn neonates (gestational age 24–40 weeks) admitted within 24 h of life were enrolled after informed parental consent. Exclusions: major congenital anomalies or lost to follow-up. Weight, length, and head circumference were recorded at birth and periodically until discharge, and plotted on Fenton 2013 and IG-21stcharts. Neonates were classified as small for gestational age (SGA; <10th centile) or appropriate (10th–90th) and screened for extrauterine growth restriction (EUGR; <10thcentile at discharge). Common neonatal morbidities were recorded. Descriptive statistics (mean±SD, median[IQR], proportions) and inferential tests (t-test or Mann–Whitney U for continuous data; chi-square/Fisher’s exact for categorical data; Cohen’s kappa for chart agreement) were applied (SPSS v30.0). A p-value <0.05 was considered significant. Results: Of 600 NICU admissions, 358 neonates met inclusion criteria. Mean gestational age was 36.5±2.6 weeks and mean birth weight 2366±620 g. Males comprised 54% (n=194). Most were inborn (85%) and delivered by cesarean section (81.3%). Forty-seven percent were term (>37 week) and 46.9% had low birth weight (1.5–2.5 kg). By Fenton charts, 29.3% (n=105) were SGA at birth vs. 30.0% (n=110) by IG-21^st (p>0.05). By discharge, EUGR (weight <10thcentile) was 49.2% (n=176) by Fenton and 50.3% (n=180) by IG-21st(p>0.05). The proportion of SGA increased markedly from birth to discharge (Fig. 2). Agreement between charts was high for weight classification (Cohen’s κ≈0.90 at all timepoints, indicating almost-perfect concordance). Neonatal complications included sepsis (64/358, 17.9%), respiratory distress syndrome (RDS, 58/358, 16.2%), bronchopulmonary dysplasia (BPD, 23/358, 6.4%), necrotizing enterocolitis (NEC, 19/358, 5.3%), patent ductus arteriosus (PDA, 15/358, 4.2%), and retinopathy of prematurity (ROP, 6/358, 1.7%). Infants with EUGR had significantly higher rates of sepsis (29.5% vs 6.6%, p<0.001), RDS (22.7% vs 9.9%, p=0.0016), BPD (11.4% vs 1.6%, p<0.001), NEC (8.5% vs 2.2%, p=0.015), and PDA (6.8% vs 1.6%, p=0.029) compared to non-EUGR infants (Table 2); ROP was rare. Birth weight was significantly lower in the EUGR group (mean 2171±626 g vs 2554±646 g; p<0.00001). These findings indicate that systemic illnesses are associated with postnatal growth faltering. Conclusion: In this NICU cohort, IG-21stcharts identified a slightly higher proportion of SGA neonates than Fenton, but both showed excellent concordance for weight measurements. Nearly half of the infants experienced EUGR by discharge. Low birth weight and serious morbidities (sepsis, RDS, BPD, NEC, PDA) were significantly associated with EUGR. Early recognition of SGA and aggressive nutritional management may improve growth outcomes. Both chart types proved useful, and clinicians should be aware that a higher incidence of EUGR is detected in NICU populations regardless of chart chosen.